Significance of radiofrequency ablation in large solid benign thyroid nodules - Lin, Yan; Shi, Yao-ping; Tang, Xiao-yin; Ding, Min; He, Yi; Li, Ping; Zhai, Bo (Frontiers in Endocrinology, 2022)
Objective: To explore efficacy and safety for radiofrequency ablation (RFA) among cases attacked by large benign solid thyroid nodules, mainly focusing on volume reduction, complication rate and thyroid function. Methods and Materials: From June 2015 to November 2019, 24 patients with 25 large benign solid thyroid nodules (more than 25mL) underwent single or sequential RFA in our institution. Eleven nodules achieved complete ablation after single RFA, while the other 14 nodules received sequential RFA. Volume reduction in large nodules was evaluated, respectively. Following single or sequential RFA, all patients received clinical and ultrasound evaluations, and the median follow-up duration among them was 23.5 months. Technical success, complication rate and recurrence rate were assessed as well. Results: In single RFA group volume reduction ranged from 62.6% to 99.4% (mean ± SD, 93.6 ±9.9%) 6 months after RFA. In sequential RFA group, volume reduction ranged from 30.6% to 92.9% (mean ± SD, 67.4 ± 17.8%) after the first RFA, and was between 83.4% and 98.4% (mean ± SD, 94.8± 3.8%) 6 months after the second RFA. The concentrations of FT3 and FT4 increased slightly 1 day after RFA and returned to normal level 1 month after. Conclusions: Single or sequential RFA is safe and effective in treating large benign solid thyroid nodules (more than 25ml) which cause obvious compressive symptoms. So compression symptoms and cosmetic conditions could be effectively improved through single or sequential RFA without marginal recurrence.